Age-dependent shifts and spatial variation in the diet of endangered Black-faced Spoonbill (Platalea minor) chicks. - Min-Su Jeong; Chang-Young Choi; Woo-Shin Lee; Ki-Sup Lee (PLoS ONE)
The endangered Black-faced Spoonbill (Platalea minor) strictly breeds in marine environments and is threatened by the rapid loss of coastal wetlands within its breeding range. Adults with chicks are thought to gradually switch feeding sites from freshwater wetlands to coastal mudflats as the chicks' osmoregulatory system develops. We investigated age-dependent shifts in the diet of Black-faced Spoonbill chicks at four breeding colonies with varying freshwater habitat availability by examining stable isotopes (δ13C, δ15N) between the tip (grown at the age of 10 days) and middle (grown at the age of 22 days) portions of their primary feathers. The δ13C value of the middle portions was significantly higher than that of the tips, which suggested that the ratio of marine resources increased with the growth and development of chicks. A Bayesian isotope mixing model revealed that the diet proportion of marine prey in the early-chick rearing season was slightly higher than in the late-chick rearing season at three colonies in inshore areas, although this proportion was approximately 60% even in the early chick-rearing period. In contrast, isotopic values and reconstructed diet composition suggested that chicks in an offshore colony with limited freshwater wetlands relied more heavily on freshwater diets for both chick-rearing periods (>80%). Our results suggest that the shifts in feeding sites seen in previous studies might be related to the age-dependent dietary shift of chicks, highlighting the importance of freshwater wetlands for spoonbills on offshore islands without an inflow of freshwater in nearby intertidal mudflats. These findings emphasize the importance of freshwater prey and wetlands even for the endangered marine-breeding spoonbills, even though the negative impact of salt stress remains inconclusive.